Phloretin Attenuates Listeria monocytogenes Virulence Both In vitro and In vivo by Simultaneously Targeting Listeriolysin O and Sortase A - Wang, Jianfeng; Liu, Bowen; Teng, Zihao; Zhou, Xuan; Wang, Xiyan; Zhang, Bing; Lu, Gejin; Niu, Xiaodi; Yang, Yongjun; Deng, Xuming (Frontiers in Cellular and Infection Microbiology, 2017)
The critical roles of sortase A (SrtA) and listeriolysin O (LLO) in Listeria monocytogenes pathogenicity render these two virulence factors as ideal targets for the development of anti-virulence agents against L. monocytogenes infection. Additionally, the structures of SrtA and LLO are highly conserved among the members of sortase enzyme family and cholesterol dependent toxin family. Here, phloretin, a natural polyphenolic compound derived from apples and pears that has little anti-L. monocytogenes activity, was identified to simultaneously inhibit LLO expression and neutralize SrtA catalytic activity. Phloretin neutralized SrtA activity by causing a conformational change in the protein’s active pocket, which prevented engagement with its substrate. Treatment with phloretin simultaneously reduced L. monocytogenes invasion into host cells and blocked the escape of vacuole-entrapped L. monocytogenes into cytoplasm. Further, L. monocytogenes-infected mice that received phloretin showed lower mortality, decreased bacterial burden and reduced pathological injury. Our results demonstrate that phloretin is a promising anti-infective therapeutic for infections caused by L. monocytogenes due to its simultaneous targeting of SrtA and LLO, which may result in fewer side effects than those caused by other antibiotics.